2021
DOI: 10.1101/2021.10.08.463638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous mnemonic and predictive representations in the auditory cortex

Abstract: Recent studies have shown that stimulus history can be decoded via the use of broadband sensory impulses to reactivate mnemonic representations. It has also been shown that predictive mechanisms in the auditory system demonstrate similar tonotopic organization of neural activity as that elicited by the perceived stimuli. However, it remains unclear if the mnemonic and predictive information can be decoded from cortical activity simultaneously and from overlapping neural populations. Here, we recorded neural ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In addition, an earlier study (Chen et al, 2015) using two-photon guided patch-clamp recordings in the primary auditory cortex of anesthetized mice suggested that the early component (0-100 ms after tone onset) of the neural response to a deviant sound may reflect neural adaptation, while the late component (200 – 400 ms after onset) may reflect deviance detection. However, while rodents can detect single deviants (Ulanovsky et al, 2003; Yaron et al, 2012) and change in acoustic features (An et al, 2021; Yang et al, 2021), to the best of our knowledge there is no direct evidence for MMR signaling in complex sound sequences, although rats can perform sequence chunking if extensively trained (Luo et al, 2021) or if the sequences are repetitive enough (Cappotto et al, 2021). It therefore remains elusive whether the primary auditory cortex, or higher order regions, can also encode deviance in more complex stimulus patterns which are more similar to natural sound sequences.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, an earlier study (Chen et al, 2015) using two-photon guided patch-clamp recordings in the primary auditory cortex of anesthetized mice suggested that the early component (0-100 ms after tone onset) of the neural response to a deviant sound may reflect neural adaptation, while the late component (200 – 400 ms after onset) may reflect deviance detection. However, while rodents can detect single deviants (Ulanovsky et al, 2003; Yaron et al, 2012) and change in acoustic features (An et al, 2021; Yang et al, 2021), to the best of our knowledge there is no direct evidence for MMR signaling in complex sound sequences, although rats can perform sequence chunking if extensively trained (Luo et al, 2021) or if the sequences are repetitive enough (Cappotto et al, 2021). It therefore remains elusive whether the primary auditory cortex, or higher order regions, can also encode deviance in more complex stimulus patterns which are more similar to natural sound sequences.…”
Section: Introductionmentioning
confidence: 98%